Molecular Profile Sensitization to House Dust Mites as an Important Aspect for Predicting the Efficiency of Allergen Immunotherapy - Rodinkova, Victoria V.; Yuriev, Serhii D.; Kryvopustova, Mariia V.; Mokin, Vitalii B.; Kryzhanovskyi, Yevhenii M.; Kurchenko, Andrii I. (Frontiers in Immunology, 2022)
House dust mite (HDM) allergens are considered to be one of the most common causes of asthma and allergic rhinitis in the world. Cysteine proteases Der p 1 and Der f 1 (group 1) and also NPC 2 family proteins Der p 2 and Der f 2 (group 2) of D. pteronyssinus and D. farinae respectively are considered the main allergens of HDMs. The difference in the sensitivity of the population to these and other allergy causing components of HDM determines the treatment strategy. Thus, the purpose of this work was to determine the pattern of sensitization of the Ukrainian population to individual allergy causing molecular components of HDM in order to improve treatment strategies for the HDM allergy in various regions of Ukraine. To determine the molecular profile of sensitization to HDM, the data of multiplex allergy test Alex2 have been obtained from 10,651 patients. The sample included 57.86% children under the age of 18 and 42.14% adults. A Python language-based statistical analysis was performed, in order to group patients by sensitization to individual molecules and their combinations, regarding the age and geographical location of the patients. Simultaneous sensitization to Der f 2 and Der p 2 allergens was the most common among the entire group Simultaneous sensitization to 5 molecules—of group 1 (Der p 1 and Der f 1), group 2 (Der f 2 and Der p 2), and Der p 23—was the second most common for entire dataset and for the children group. This pattern differed in adults, where monosensitization to Der p 23 occupied the second position, suggesting that this molecule is an important factor of HDM allergy in Ukraine. Of the 16 analyzed regions, sensitization to Der p 23 prevailed in 2 Western regions of Ukraine. In the rest of the regions combination of Der p 2 and Der f 2 was the most prevalent. The established character of population sensitization to HDM in Ukraine is a good prognostic marker of allergen immunotherapy (AIT) efficacy.